2013
DOI: 10.1080/17437199.2013.855592
|View full text |Cite
|
Sign up to set email alerts
|

Developing an integrated biomedical and behavioural theory of functioning and disability: adding models of behaviour to the ICF framework

Abstract: It is concluded that these models offer a better explanation of functional outcomes than the ICF alone and could form the basis for the development of improved models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 87 publications
4
8
0
Order By: Relevance
“…Interestingly, these authors also hypothesized that non-volitional determinants such as impairments are more strongly related to measures of limitations and capacity, whereas volitional determinants are more strongly related to measures of performance, in this case participation in physical activity. 42 This is very much in line with recent studies 24,25 looking at factors associated with participation in physical activity. A focus on problem solving, self-efficacy, and the presence of positive personal and environmental factors seems crucial for participation in physical activity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, these authors also hypothesized that non-volitional determinants such as impairments are more strongly related to measures of limitations and capacity, whereas volitional determinants are more strongly related to measures of performance, in this case participation in physical activity. 42 This is very much in line with recent studies 24,25 looking at factors associated with participation in physical activity. A focus on problem solving, self-efficacy, and the presence of positive personal and environmental factors seems crucial for participation in physical activity.…”
Section: Discussionsupporting
confidence: 83%
“…In this model, the intention of being physically active is the central determinant for participation in physical activity, with aspects such as attitude, self‐efficacy, health condition, and facilitators and barriers as personal components, and social influence and facilitators and barriers as external components. Using a combination of behavioural models and the ICF is also recommended by Johnston and Dixon . These authors tested the prediction of behaviour using the ICF, behavioural models, and a combination of the ICF and behavioural models, and found that the combination performed best in predicting behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, beliefs about capabilities have been shown to influence what people do and how they engage in life situations (14), with applicability to rehabilitation (15). The results from this study therefore support the proposals that considering participation as a therapeutic outcome may benefit from considering participation as human behaviour (15)(16)(17), and that therapists should explicitly consider human behavioural factors when designing therapy interventions (12). The results further expand the existing literature by identifying and illustrating specific ways in which behaviour change techniques and change processes may be present in children's therapy.…”
Section: Discussionsupporting
confidence: 77%
“…However, several authors have commented on the need for further elaboration of the participation construct and for clarification of the relationships between the constructs in a theoretical framework that can integrate theory over the several disciplines that investigate participation. Psychological theory has been successfully integrated with biomedical explanations of activity limitations resulting in better prediction and understanding of why and when individuals experiencing impairments may be limited (Johnston & Dixon, ). The current findings suggest that models of self‐regulation, such as Carver and Scheier's Control Theory (), may indicate how individuals faced with acquired impairments such as deficits in emotion regulation, identify goals (such as managing emotions) compatible with their higher order values of social participation in life situations and engage in self‐regulatory strategies to achieve these goals, with resulting impact on positive and negative emotions.…”
Section: Discussionmentioning
confidence: 99%